Local and Remote Sources of Airborne Suspended Particulate Matter in the Antarctic Region - Marina Montes, César; Pérez Arribas, Luis Vicente; Anzano, Jesús; Cáceres, Jorge Omar (Atmosphere, 2020)
Quantification of suspended particulate matter (SPM) measurements—together with statistical tools, polar contour maps and backward air mass trajectory analyses—were implemented to better understand the main local and remote sources of contamination in this pristine region. Field campaigns were carried out during the austral summer of 2016–2017 at the “Gabriel de Castilla” Spanish Antarctic Research Station, located on Deception Island (South Shetland Islands, Antarctic). Aerosols were deposited in an air filter through a low-volume sampler and chemically analysed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES). Elements such as Al, Ca, Fe, K, Mg, Na, P, S, Cu, Pb, Sr, Ti, Zn, Hf, Zr, V, As, Ti, Mn, Sn and Cr were identified. The statistical tools together with their correlations (Sr/Na, Al/Ti, Al/Mn, Al/Sr, Al/Pb, K/P) suggest a potentially significant role of terrestrial inputs for Al, Ti, Mn, Sr and Pb; marine environments for Sr and Na; and biological inputs for K and P. Polar contour graphical maps allowed reproducing wind maps, revealing the biological local distribution of K and P (penguin colony). Additionally, backward trajectory analysis confirmed previous affirmations and atmospheric air masses following the Antarctic circumpolar pattern. Ministerio de Ciencia, Innovación y Universidades (España) Gobierno de Aragón Depto. de Química Analítica Fac. de Ciencias Químicas TRUE pub